Incidence of iron deficiency anaemia in pregnant women after microcytic hypochromic anaemia: Prospective matched cohort study in Kisangani, Democratic Republic of the Congo - Soda, Martin; Lufuluabo, Jean Kasuyi; Ilombe , Gillon; Batina, Salomon Agasa; Lutumba , Pascal (Orapuh Journal, 2025)
IntroductionIron deficiency anaemia (IDA) in pregnant women is a major public health challenge. The incidence of IDA increases throughout pregnancy, and women who experience it are at a similar risk of recurrence in subsequent pregnancies or even during the same pregnancy.PurposeThis study aimed to determine the incidence of iron deficiency anaemia in pregnant women with microcytic hypochromic anaemia compared with pregnant women with non-microcytic hypochromic anaemia.MethodsA prospective, open-label, multicentre, matched cohort study was conducted with 11,226 pregnant women, comprising 7,832 (69.77%) with microcytic hypochromic anaemia and 3,394 (30.23%) with non-microcytic hypochromic anaemia. These women were enrolled and monitored for 66 days in antenatal clinics (ANC) across 17 selected health facilities (HF) in Kisangani.ResultsThe overall incidence of iron deficiency anaemia was 2.52% (95% CI: 2.47, 2.57) among all pregnant women. Women with microcytic hypochromic anaemia had a higher risk of developing iron deficiency anaemia compared to those with non-microcytic hypochromic anaemia (2.79% vs. 1.91%). Predictors of iron deficiency anaemia in pregnancy included microcytic hypochromic anaemia (aHR = 1.33; 95% CI: 1.26–1.40), age between 20 and 35 years (aHR = 1.19; 95% CI: 1.07–1.34), non-use of insecticide-treated nets (ITNs) (aHR = 1.11; 95% CI: 1.04–1.19), and iron supplementation during pregnancy (aHR = 1.14; 95% CI: 1.06–1.21).ConclusionThe findings highlight the importance of preventing the progression of anaemia in pregnancy through improved reproductive health services.